Mejora de Induprom S.A.C. a través de la manufactura esbelta - Romero Luciano, Claudia Fiorella (2021)
In this work, an improvement analysis focused on the company INDUPROM S.A.C. was carried out, in order to determine the impact caused after the application of lean manufacturing methodologies to the double handle production process of the aforementioned company. In Chapter I, the main activity of the company is written, which produces elements of wood, metal and plastics, which provides the panorama of the processes to be studied, which will be the production area of double handles. On the other hand, in Chapter II, the existing problem of the company INDUPROM S.A.C is defined, identifying that the problem is the level of defectives, since it mainly affects quality, productivity and the use of time. Then, in Chapter III, the theoretical framework is established, where the tools and techniques to be used in lean manufacturing are defined. It also presents the investigations related to the company, as well as the plastics industry. In addition, in chapter V, the production process is described, which includes the operations diagram, as well as the value flow map to later carry out the root cause analysis and finally propose the most appropriate solution, making the economic evaluation, social and environmental. Similarly, Chapter VI discusses the results of the solution proposed in Chapter V, analyzing the annual costs before and after applying lean manufacturing. Finally, in chapter VII the conclusions corresponding to the improvement applied through lean manufacturing are made.